ALOKASI PEKERJA PADA SUATU PROYEK DENGAN METODE HUNGARIAN (STUDI KASUS: PT. IRA WIDYA UTAMA MEDAN) - Eferoni Ndruru; Fince Tinus Waruwu; Anda Yanny (STMIK Budi Darma, 2017)
The allocation of workers is very much needed by the company. But in reality the company is difficult to place employees in every allocation. But with the development of existing technology, it can be minimized by calculating the cost of each worker and each allocation by utilizing existing data and extraction to generate new knowledge. Implementation of operational research techniques using hungarian methods and tested using a system or application as a decision tree to assign some decent workers to be placed on existing jobs within the company. The extension process can show the group of employee data that fall into the category of workers and the allocation so as to optimize the costs that are out by the company. So PT.Ira Widya Utama Medan can be a reference to take decisions in assigning and allocating employees next.